IMPAIRED BETA-2ADRENERGIC ENDOTHELIUM-DEPENDENT VASODILATION IS REVERSED BY PHOSPHODIESTERASE INHIBITION IN PATIENTS PREVIOUSLY HOSPITALIZED WITH COVID-19. (June 2022) - Faconti, Luca; Farukh, Bushra; McNally, Ryan; Brett, Sally; Chowienczyk, Philip
Abstract : Objective: Endothelial dysfunction is thought to underlie many of the complications of COVID-19 but to what degree this persists after recovery is unknown. Here we examine endothelial function in subjects previously hospitalized with COVID-19, those with mild symptoms who were not hospitalized and negative controls (absence of SARS-CoV-2-antibodies). Endothelial function was measured as pulse wave response to the 2 adrenergic agonist salbutamol (PWRS) which is mediated through the nitric oxide - cyclic guanosine monophosphate pathway (NO-cGMP). Design and method: Echocardiography was used to exclude subjects with cardiac abnormalities. Tonometry of the radial artery (SphygmoCor, AtCor Medical, Sydney, Australia) was performed in duplicate by a single operator before and after inhalation of 200 mcg of salbutamol using a spacer device. The PWRS was taken as the change from baseline in augmentation index (Aix) as calculated by the SphygmoCor system. In a sub-sample, PWRS was assessed in the presence and absence of the phosphodiesterase type 5 inhibitor sildenafil which inhibits the breakdown of cGMP. Results: We recruited 88 subjects (49 men) aged 47.9 ± 14.3 (mean ± SD) years of whom 32 were previously hospitalized with COVID-19 ( 6 months). Subjects previously hospitalized with COVID-19 were all previously assessed in a dedicated pulmonary clinic. Age, gender, BMI, smoking status, diabetes and estimated 10-year cardiovascular risk (Q-RISKâ3) were similar between the groups. Administration of salbutamol reduced AIx in controls and those with mild COVID-19 but produced an increase in AIx in previously hospitalized COVID-19 cases (mean [95% CI]): -2.85 [-5.52, -0.188] %, -2.32 [-5.17, 0.54] %, and 3.03 [0.06, 6.00] % respectively, P = 0.017 between the groups. In a sub-sample (11 hospitalized and 11 non-hospitalized) the PWRS was measured again 30 minutes after oral administration of sildenafil 25 mg. This produced a greater reduction in AIx: -5.28 [-9.00, -1.54] % in non-hospitalized and a reduction: -3.90 [-7.60, -0.21] % in hospitalized patients, and an overall improvement in the PWRS (P = 0.006). Conclusions: In subjects previously hospitalized with severe COVID-19, endothelial function is impaired for many months after hospital discharge and the impaired NO-cGMP mediated vasodilation may be reversed by sildenafil.